Microwave Heating - Electromagnetic Fields Causing Thermal and Non-Thermal Effects 2021
DOI: 10.5772/intechopen.96092
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Bioactive Compounds (Review)

Abstract: In recent times, bioactive compounds from plant samples are extracted using a microwave extractor. This is because traditional methods of extraction are need of higher volume of solvents, degrade thermal-sensitive bioactive compounds, and consume much time of extraction. Hence, this chapter unveils the importance of the microwave-assisted extraction (MAE) technique in the recovery of bioactive compounds from plants. The involving extraction steps need to recover higher yields, faster, consumption of lesser ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The MAE is one of the modern extraction methods that has received much patronage due to several merits such as a reduction in utilization of solvents, enhanced yield recovery, better selectivity, reproducibility, reduced operation time, and less sample manipulation Nour et al, 2021). MAE utilizes microwave energy for faster heating which results from a range of electromagnetic spectrums of light (300 MHz to 300 GHz) with short wavelengths usually between 1 cm −1 and 1 m −1 .…”
Section: Methanol Leavesmentioning
confidence: 99%
“…The MAE is one of the modern extraction methods that has received much patronage due to several merits such as a reduction in utilization of solvents, enhanced yield recovery, better selectivity, reproducibility, reduced operation time, and less sample manipulation Nour et al, 2021). MAE utilizes microwave energy for faster heating which results from a range of electromagnetic spectrums of light (300 MHz to 300 GHz) with short wavelengths usually between 1 cm −1 and 1 m −1 .…”
Section: Methanol Leavesmentioning
confidence: 99%
“…The fact that the extracts from untreated SOMW samples exhibited the highest yield for both water and methanol indicates that moisture works in conjunction with polar solvents, thus enhancing the extraction of the desirable compounds [37]. Moreover, high EYs The fact that the extracts from untreated SOMW samples exhibited the highest yield for both water and methanol indicates that moisture works in conjunction with polar solvents, thus enhancing the extraction of the desirable compounds [37]. Moreover, high EYs were observed for both solvents after 10 min of extraction, proving that both solvents could penetrate and recover the bioactive compounds in reduced times.…”
Section: Ultrasound-assisted Extraction (Uae)mentioning
confidence: 99%
“…Electromagnetic energy causes the evaporation of water from the plant's matrix, causing a considerable pressure and the deformation of the cellular and subcellular walls. This deformation brings structural changes in the plant matrix, thus generating an increased mass transfer of dissolved substances as a result of cell destruction, and thus facilitating the extraction of tannins from the plant cell matrix [5][6][7]. Figure 5 shows a significant interaction effect on the extraction of catechin from spinosa branches.…”
Section: Figurementioning
confidence: 99%
“…Large samples or aggregated small particles cannot be heated uniformly. Also, a cooling time is necessary after MAE [5][6][7]. Yingngam et al showed that the MAE process accelerates the mass transfer rate and improves the extraction yield of triterpenes from leaves of C. asiatica, while consuming less solvent [8].…”
Section: Introductionmentioning
confidence: 99%